STIGMA-STATISTIK: Når dagsordener sættes i dansk aids-politik - Seeberg, Jens (Tidsskriftet Antropologi, 1996)
Jens Seeberg: Stigma Statistics: Agendas in the Making in Danish AIDS Policy This article explores a number of paradoxes and assumptions in the public debate on AIDS in Denmark. They form part of a recurrent attack on the Danish ‘soft line’ AIDS policy that maintains anonymity and voluntary HIV-testing. One central issue in recent years has been obligatory testing of asylum seekers from high risk areas as a precondition for considering the asylum request. Especially asylum seekers from African countries are pointed out as constituting a major threat to the native Danish population in terms of spread of HIV. This is shown to rest on a misreading of the official statistics, repeated as often as the statistics themselves. The assumption that there is a basic clash between the human rights of the HIV-infected person and the population in general is discussed. This conceived clash rests on the assumption that restrictions of the human rights of the HIV-infected person will provide efficient protection for the noninfected majority. The potential counterproductive effects of this line of thought are discussed. Contact tracing is sometimes considered as an effective preventive measure. Part of the critique of the present AIDS policy States that contact tracing is virtually non-existing and that this has a major negative impact on the preventive efforts. It is argued that while the impact of contact tracing in itself may be rather limited, the lack of contact tracing may be seen as a symptom of insufficient counselling. While obligatory HIV testing may never be practiced in Denmark, its recurrent appearance on the agenda serves to provoke a defensive stand among AIDS policy makers. It is argued that this debate has hitherto had the effect of keeping the needs of HIV-infected people - and especially HIV-infected immigrants — away from public debate and serious concern.